(untitled) (Journal of Education, Humanities, and Social Research, 2025)
This study explored the relationship between ideological practices and civic engagement among university students. It assessed profiles, perceptions of ideological practices, and civic engagement levels across dimensions like knowledge, identity, and participation. While practices were generally rated as "Practiced," areas like real-world applications require improvement. Civic engagement was moderate, with strengths in identity and responsibility but gaps in knowledge. Senior students showed lower engagement levels. A modest correlation was found, with innovative teaching and subject integration enhancing skills and identity. The study highlights the need for experiential, interdisciplinary, and senior-focused programs to foster socially responsible, civically engaged graduates.